2012
DOI: 10.1093/icvts/ivs184
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative quality of life on mortality after isolated elective myocardial revascularization

Abstract: Based on these results, we conclude that, in isolation, poor low preoperative EQ-5D and EQ-VAS scores do not contribute to deciding which patients should undergo cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It is comparable with the 71.4% inclusion in the study of Rumsfeld and much higher than a recent published study by Bramer et al, who had only had only about 40% of the patients with pre- and postoperative QoL information [5,11]. However lower than in a previous study where we had roughly 75% inclusion and the recent study of KH Gjeilo et al, which had circa 91% inclusion [4,12]. It is difficult to compare these percentages of inclusion, though, since several publications make no mention of such data and the method and criteria of inclusion and exclusion are also determining [6].…”
Section: Discussionsupporting
confidence: 76%
“…It is comparable with the 71.4% inclusion in the study of Rumsfeld and much higher than a recent published study by Bramer et al, who had only had only about 40% of the patients with pre- and postoperative QoL information [5,11]. However lower than in a previous study where we had roughly 75% inclusion and the recent study of KH Gjeilo et al, which had circa 91% inclusion [4,12]. It is difficult to compare these percentages of inclusion, though, since several publications make no mention of such data and the method and criteria of inclusion and exclusion are also determining [6].…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, the lowest scores in the physical component, as seen in other studies (3,18) , may reflect the impact of cardiovascular illnesses on individuals' role-physical aspects.…”
Section: Discussionmentioning
confidence: 64%
“…This can show the relevance of these factors in possibly facing cardiovascular illnesses, associated with higher scores in the mental component (6,18) . In contrast, the lowest scores in the physical component, as seen in other studies (3,18) , may reflect the impact of cardiovascular illnesses on individuals' role-physical aspects.…”
Section: Discussionmentioning
confidence: 85%
“…7 A number of studies have evaluated the association between preoperative quality of life measures and outcomes after cardiac surgery. [8][9][10][11][12][13][14][15] Rumsfeld et al 16 previously reported that health-related quality of life (HRQoL), using the Veterans RAND Short Form-36 (VR-36), was an independent predictor of post-CABG 6-month mortality. While HRQoL metrics are now commonly used in comparing treatments in large-scale surgical trials, the use of such tools in daily clinical practice for predicting patient-specific risk continues to be quite limited.…”
Section: Introductionmentioning
confidence: 99%